Logging has legacy effects on the structure of soil fungal communities several decades after cessation in Western Cascade forest stands - Spencer, Max W.; Roy, Bitty A.; Thornton, Tiffany E.; Silva, Lucas C. R.; McGuire, Krista L. (Frontiers in Forests and Global Change, 2023)
Logging impacts millions of hectares of forests globally every year, and not only affects tree cover, but also disrupts below-ground soil communities that are essential for forest ecosystems. Soil fungi are particularly vulnerable to such disturbances due to their reliance upon plant hosts as their source of carbon. Fluctuations within the major guilds of fungi important for forest function can have ramifications for plant communities and biogeochemical processes. We addressed questions about soil fungal communities in temperate forest stands with varying logging histories: 1) do assembly patterns of soil fungal communities and functional guilds reflect historical differences in logging legacies? 2) does sequencing of below-ground communities of fungi resemble the composition of surveys of fungal fruiting bodies? 3) how do fungal communities in the litter layer differ from those in the soil and do these assembly patterns change with logging history? Our study took place in the HJ Andrews Experimental Forest in western Oregon, USA. We sampled soil and litter (Oi – Oe) in three sites with different logging histories: one clear cut in 1974, one selectively logged and thinned three times between 1974 and 2001, and one unlogged. We sequenced soil fungi separately for mineral soil samples and litter samples. Additionally, we compiled fruiting-body studies from 1972 through the present to compare with our eDNA samples. We found that four decades after logging had ceased there were detectable signatures within the soil fungal communities that distinguished logged from unlogged sites, indicating a legacy that affects many generations of fungi (PERMANOVA; p < 0.001 for both soil and litter fungi). There were also significant differences between litter and mineral soil communities (PERMANOVA; p < 0.001) with higher relative abundances of pathogens within the litter layer and a greater proportion of mycorrhizal fungi in the soil. These results highlight the importance of including forest litter in studies, as entire guilds of fungi can be underestimated when considering a single fraction. Together, these results have repercussions for the regeneration of forests following logging, as the composition of fungal guilds important to plant functions do not fully recover even after decades of cessation.